'Agro sí, mina NO!' the Tía Maria copper mine, state terrorism and social war by every means in the Tambo Valley, Peru. (May 2019) - Dunlap, Alexander
Abstract: The Tía Maria copper mine situated above the agricultural Tambo Valley, southwest Peru, has sparked nearly ten years of protracted conflict. This conflict began in 2009, yet Southern Copper Peru or Southern, a subsidiary of Grupo Mexico, has faced ardent resistance. This article explores the 'political reactions from above', examining how Southern and the Peruvian government have negotiated the popular rejection of the mine. Residents have organized a popular consultation, large-scale demonstrations, road blockades and general strikes, which has been met with violent repression. Reviewing the political ecology of counterinsurgency, which studies the socio-ecological warfare techniques employed to control human and natural resources, and relating it to social war discourse, this section lays the theoretical foundations to discuss the coercion and 'social war component' present in natural resource extraction. This leads to an overview of the relationship between Peruvian security forces and extraction industries, followed by a brief chronology of the Tía Maria conflict. The subsequent two sections offer a political ecology analysis of various 'hard' and 'soft' counterinsurgency techniques employed by the Peruvian state and Southern in an attempt to pacify social unrest and socially engineer acceptance of the project. The concluding section discusses the 'whole-of-government' counterinsurgency approach employed, recognizing how the present institutional arrangements and business imperatives are designed to override popular socio-ecological concerns. Supporting social war discourse, the article contends that the state apparatus and politics itself serve as an instrument of social pacification and ecological exploitation regardless of widespread ecological and climatic concerns.